Characteristics of a multicolor dye laser - Burlamacchi, P. (1979)
An experimental investigation on the possibility of obtaining tunable, multiple wavelength output in mixture of dyes pumped by a nitrogen laser has been carried out. A great number of binary dye mixtures have been tested. Simultaneous two wavelength operation is generally possible provided the gain profiles of both dyes are neither strongly overlapped nor too widely separated. Three color emission is feasible in many mixtures, but the possible combinations are limited. A simple scheme for multiple, simultaneous wavelength tuning is presented.